Case on Importance of Strategic Location - Nur Syazwani, Ahmad (Penerbit UMP, 2017)
Location has the key effect on the overall risk and income for every industry. Location decision effects on costs, both fixed and variable. The location decision often is contingent on,the type of company. For industrial location decisions, the strategy is typically reducing costs, although creativity and innovation should also be serious. For retail and techinal service organizations, the approach focuses on exploiting revenue. Warehouse location strategy, however, may be driven by a combination of speed of delivery and costs.